ANALISIS TEKS DAN KODE INTERIOR GEREJA KARYA TADAO ANDO "Church of The Light" dan "Church on the Water" - Kusumarini, Yusita (Dimensi Interior, 2006)
"Church of The Light" and "Church on The Water" are interior creations with spiritual meaning. Symbols and signs in the interior design of the churches express the spiritual meaning. Everything that visible in the interior of the churches being texts and codes. Texs and codes can be analize to get the spiritual meaning of the churches. Teori of text and code in the space and architecture semiotic be an alternative media to get the meaning of interior object according to visual. The meaning that can get from text and codes analysis of the churches are simplicity, smoothness, integrity, philosophize with media of nature, pattern with space disguised, and posmodern style. Abstract in Bahasa Indonesia : Interior gereja "Church of The Light" dan "Church on The Water" adalah karya yang penuh makna secara spiritual. Makna spiritual gereja terekspresikan melalui simbol dan tanda dalam desain ruangnya. Apa yang nampak secara visual dalam ruang gereja tersebut menjadi teks dan kode yang dapat dianalisis untuk membaca makna spiritual yang ada. Teori teks dan kode dalam semiotika ruang dan arsitektur menjadi salah satu alternatif media analisis untuk membaca makna sebuah objek interior secara visual. Makna yang terbaca dari analisis teks dan kode interior gereja "Church of The Light" dan "Church on The Water" adalah sederhana, polos, jujur, berfilosofi dengan media alam, berpola spasial tersamar, dan berstruktur gaya posmodern. Kata kunci: teks, kode, interior, gereja.